Reflecting Forewords - and Chambers, Robert; Lewin, Tessa (Practical Action Publishing, 2024)
Reflecting Forewords is an unashamedly ambitious book. Full of lessons from the past that are relevant for the future, it is a compilation of inspiring forewords from books written by Robert Chambers; one of the most influential and prolific scholars to write about participation, poverty, and knowledge in development studies. Tessa Lewin, Robert’s colleague and an experienced practitioner and researcher, has worked with Robert to weave together the forewords alongside a series of reflections from other practitioners and scholars in the field. In our world of dramatic unforeseeable change, Reflecting Forewords seeks to draw lessons and present insights that should not be ephemeral, but can contribute on a lasting way to policy, practice and research in the rest of our 21st century. Readers will draw their own conclusions. The orientation is forward-looking into our unpredictable future, stressing the need to be alert, in touch, nimble, and guided by reflexivity. This curated collection of resurfaced gems will inspire development professionals, teachers and graduate students of development studies, policymakers, historians of development thinking and practice, activists, and all those who are concerned with a better life for all.